Improving Students’ Speaking Ability by Using Describing Pictures at the First Year of SMK Negeri 3 Enrekang - Hasan, Hasan; Aminullah, Aminullah; Ismail, Ismail; Firdiani, Dian (Universitas Muhammadiyah Enrekang, 2022)
This research studies about improving students’ speaking ability by using describing pictures at the first year of SMK Negeri 3 Enrekang. The problem statement of this research was “does the use of describing pictures improve the students speaking ability at the first year of SMK Negeri 3 Enrekang. The objective of this research was intended to know whether or not using describing pictures can improve the students’ speaking ability at the first year of SMK Negeri 3 Enrekang. This research applied quasi experimental method with one class of experimental group and one class in control group. The researcher used pre-test and post-test in collecting data. The research sample was the students of the first year they were Administrasi Perkantoran 1 and administrasi perkantoran 2. Class consists of 20 students, so the researcher took probability sample that was cluster sampling technique. The data analyzed by finding the mean score. For collecting data, the researcher used instrument namely oral test to measure the students’ speaking ability. The result of this research showed that the student’ speaking ability was low classification in pre-test with the mean score 56.34 for experimental class and the mean score of control class was 52.74 and it was poor categorized. However after doing the treatment by using describing pictures they got good classification for experimental group (73.28) and still poor for control group (55.78) in post-test. The data was analyzed by using T-test and the result showed that the T-test value (7.023) was higher than T-table (2.042). It means that there was a significance different of students’ speaking ability before and after the treatment through the application of describing pictures. It concluded that describing pictures can be used in improving speaking ability of the students.